Osmotic dehydration under high hydrostatic pressure: Effects on antioxidant activity, total phenolics compounds, vitamin C and colour of strawberry (Fragaria vesca) - Nuñez Mancilla, Yissleen (2013)
Simultaneous application of osmotic dehydration under high hydrostatic pressure conditions of strawberries was studied with the purpose of analyzing the effect of the combined process on the antioxidant capacity, phenolic compounds, colour and vitamin C of strawberries during refrigerated storage. The osmotic solution was prepared using commercial sugar at 40 Brix. Samples were pressurized between 100 and 500 MPa for 10 min. The radical scavenging activity showed higher antioxidant activity at 400 MPa rather than at low pressure (100, 200 and 300 MPa). The total phenolic content increased with pressure presenting a maximum at 400 MPa. Pressurized samples retained vitamin C content. Based on these results, working at 400 MPa for 10 min ensures physicochemical and high levels of nutritional parameters in osmo-dried strawberries.